2016
DOI: 10.1155/2016/8741632
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Testicular Infarction, an Underdiagnosed Entity: Case Report with Histopathologic Correlation and Review of the Diagnostic Features

Abstract: A 30-year-old male presented with a 1-day history of left scrotal pain and a tender left testicle and epididymis on physical exam. Scrotal ultrasound showed an avascular, heterogeneous, hypoechoic lesion in the superior left testis suggestive of infarction or neoplasm. The patient was managed conservatively; however, his pain continued and follow-up ultrasound 6 days later showed interval increase in the size of the mass. Left radical orchiectomy was done and pathology result showed segmental infarction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…At the early stage intervening vascular structures might be depicted between the avascular parenchymal lobules, corresponding to centripetal arteries. [9] After the first 24 hours a peripheral hyper emic rim can be seen on colour Doppler US, which probably corresponds to inflammatory changes, granulation tissue and compressed parenchymal vessels. [7] In our case there were no signs of inflammation or granulation tissue in the periphery of the lesion on microscopic examination, however, congestive vessels and sclerotic spermatic tubules could be depicted.…”
Section: Discussionmentioning
confidence: 98%
“…At the early stage intervening vascular structures might be depicted between the avascular parenchymal lobules, corresponding to centripetal arteries. [9] After the first 24 hours a peripheral hyper emic rim can be seen on colour Doppler US, which probably corresponds to inflammatory changes, granulation tissue and compressed parenchymal vessels. [7] In our case there were no signs of inflammation or granulation tissue in the periphery of the lesion on microscopic examination, however, congestive vessels and sclerotic spermatic tubules could be depicted.…”
Section: Discussionmentioning
confidence: 98%
“…Epididymo-orchitis is considered to be the most common underlying cause of the condition [ 2 ]. Some identified risk factors include polycythemia [ 3 ], intimal fibroplasia of the spermatic artery [ 4 ], sickle cell disease [ 5 ], and trauma [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that within the first 24 hours, the 2D gray scale does not immediately detect the lesioned area, which may be essentially the same as the normal testicular parenchymal echo, but with both active and inactive parenchyma present in the lesioned area, and color Doppler examination reveals a marked reduction or loss of blood flow signal in the lesioned area and a surrounding normal testicular the parenchymal blood flow signal was slightly increased [5] . As the disease progressed after 24 hours, gray-scale ultrasound showed heterogeneous echogenicity and hypoechogenicity in the lesioned area, and color Doppler ultrasound revealed a surrounding hyperemic rim, which may correspond to inflammatory changes, granulation tissue, and compressed parenchymal vessels [5 , 10] . Currently, with the development of contrast-enhanced ultrasound technology, its characteristic presentation of testicular lesions is also instrumental [5] .…”
Section: Discussionmentioning
confidence: 99%